(1090) On Solving the Capacitated Facilities Location Problem with Concave Cost Functions حول حل مشكلة تحديد مواقع المنشآت ذات السعة المحدودة مع دوال التكلفة المقعرة - Al - Walid N. E l-Shafei. (INP., 2020)
The problem of location central facilities on a network has recently received considerable interest.In part I of this paper on search procedure which is designed for problems in which there are economics of scale, capacity and configuration restrictions on the various sites is given. For the state case, several algorithms were derived to handle two various of the problem, i.e, when the concave cost function replaced by (a) many linear segment and (b) one linear segment. For the dynamic case, the interaction of many economic accounting and technological factors effects the problem formulation and hence the solution approach.In part II of this paper, algorithmic aspects of the search procedures as applied to each version of the problem will be given together with some computational experiences.